2022
DOI: 10.18517/ijaseit.12.6.16903
|View full text |Cite
|
Sign up to set email alerts
|

Flood Vulnerability Evaluation and Prediction Using Multi-temporal Data: A Case in Tangerang, Indonesia

Abstract: Land-use change has an impact on growing physical flood vulnerability. Geographic Information System (GIS) and Analytic Hierarchy Process (AHP) approaches are increasingly being used for flood vulnerability assessments. However, none has used timeseries land cover data for evaluation and rainfall over various return periods for prediction simultaneously, especially in Indonesia. Therefore, this study aims to evaluate and predict physical flood vulnerability using time-series land cover data and rainfall data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…These findings serve as a basis for predicting the future distribution of hydrological parameters resulting from ongoing land use changes. Santosa et al [22] found that land use change directly contributes to increased flood vulnerability in a watershed. Wardhani et al [16] observed that land use change had occurred in a watershed adjacent to the study area, mostly converting land into settlements and agricultural areas.…”
Section: Discussionmentioning
confidence: 99%
“…These findings serve as a basis for predicting the future distribution of hydrological parameters resulting from ongoing land use changes. Santosa et al [22] found that land use change directly contributes to increased flood vulnerability in a watershed. Wardhani et al [16] observed that land use change had occurred in a watershed adjacent to the study area, mostly converting land into settlements and agricultural areas.…”
Section: Discussionmentioning
confidence: 99%
“…For the composite flood susceptibility index of the selected study area, five categories-very high, high, moderate, low, and very low-of flood susceptibility were recognized. A weighted overlay analysis was assigned here following the techniques used by various studies, including [71][72][73][74][75][76][77], to determine the flood vulnerability and susceptibility in GIS, specifically in coastal and cyclone-prone areas. According to its definition, weighted overlay is an approach to modeling suitability.…”
Section: Multi-criteria Decision-making-analytical Hierarchy Process ...mentioning
confidence: 99%